A non-invasive method for the characterisation of milk protein foams by image analysis. (November 2016) - Ewert, Jacob; Claaßen, Wolfgang; Glück, Claudia; Zeeb, Benjamin; Weiss, Jochen; Hinrichs, Jörg; Stressler, Timo; Fischer, Lutz
Abstract: An apparatus for the investigation of milk protein foams was introduced based on three jacket columns and exclusively image analysis. The method had a repetition coefficient <10%, and offered a high sample throughput and an expandable design. Sodium caseinate, micellar casein concentrate, whey protein isolate and whey protein concentrate foams were analysed as an application. Foaming properties depended on the protein, the composition of the preparations and the foaming conditions, e.g., stable foams at 20 °C were observed for micellar casein, while sodium caseinate showed a half-life of 22 min. At 50 °C, the stability of sodium caseinate decreased by about 70%. Additionally, a direct link between the foaming properties of sodium caseinate and its degree of enzymatic hydrolysis was found. No changes in foaming properties using Alcalase ® 2.5L occurred up to a degree of hydrolysis of about 3%, while higher degrees of hydrolysis led to decreased foaming properties.